Global Financial Regulatory Reforms:Implications for Developing Asia - Douglas W. Arner; Cyn-Young Park (Asian Development Bank (ADB), 2010)
The objective of global regulatory reform is to build a resilient global financial system that can withstand shocks and dampen, rather than amplify, their effects on the real economy. Lessons drawn from the recent crisis have led to specific reform proposals with concrete implementation plans at the international level. Yet, these proposals have raised concerns of relevance to Asia's developing economies and hence require further attention at the regional level. We argue that global financial reform should allow for the enormous development challenges faced by developing countries—while ensuring that domestic financial regulatory systems keep abreast of global standards. This implies global reforms should be complemented and augmented by national and regional reforms, taking into account the very different characteristics of emerging economies' financial systems from advanced economies. Key areas of development focus should be (i) balancing regulation and innovation, (ii) establishing national and cross-border crisis management and resolution mechanisms, (iii) preparing a comprehensive framework and contingency plan for financial institution failure, including consumer protection measures such as deposit insurance, (iv) supporting growth and development with particular attention to the region's financial needs for infrastructure and for SMEs, and (v) reforming the international and regional financial architecture.
hdl:11540/1943
Keywords: E61; G28; 330; financial regulatory reform; global financial architecture; G-20; Asia; national and regional reform